2017
DOI: 10.1037/gpr0000133
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Regulatory Focus Based on Four Regulatory Forms

Abstract: This study employs the four regulatory forms (goal pursuit, goal maintenance, negative escape, and active avoidance), to illuminate the heterogeneousness among regulatory focus measurements and activations. The first two studies consistently found that promotion focus involves goal pursuit orientation; however, prevention focus encompasses a goal maintenance and a negative escape orientation. The regulatory forms were then applied to regulatory fit research to investigate how the matches of regulatory forms de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 62 publications
(185 reference statements)
0
7
0
Order By: Relevance
“…In addition, Studies 1 and 2 both used the same manipulation of regulatory focus. As experimental manipulations often only pertain to certain aspects of the theoretical concept to be operationalised (e.g., Chen & Bei, 2017), conceptual replications with different manipulations are vital to ensure that the concept is indeed grasped—the respective shortcomings of each method cancelling each other out by force of repetition (see Webb et al., 1966). In Study 3, we therefore turned to a different regulatory focus manipulation, which we describe below.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Studies 1 and 2 both used the same manipulation of regulatory focus. As experimental manipulations often only pertain to certain aspects of the theoretical concept to be operationalised (e.g., Chen & Bei, 2017), conceptual replications with different manipulations are vital to ensure that the concept is indeed grasped—the respective shortcomings of each method cancelling each other out by force of repetition (see Webb et al., 1966). In Study 3, we therefore turned to a different regulatory focus manipulation, which we describe below.…”
Section: Discussionmentioning
confidence: 99%
“…(e.g.,Chen & Bei, 2017), conceptual replications with different manipulations are vital to ensure that the concept is indeed grasped-the respective shortcomings of each method cancelling each other out byF I G U R E 2 Decision times (in ms) in the go/no-go lexical decision task as a function of focus and regulatory closure in Study 2. Error bars represent 95% confidence intervals.force of repetition (seeWebb et al, 1966).…”
mentioning
confidence: 99%
“…This is because prevention focus initiates cognitive control resources to avoid failure (Ståhl et al, 2012). Prevention focus entails a goal maintenance orientation, such as avoiding the absence of the desired reference (Chen & Bei, 2017). Making progress toward achieving goals enhances feelings of personal control (Lin et al, 2020; Thompson, 2002).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Previous studies have found that reverse-worded items may cause a problem in measurement (Babin & Griffin, 1998;Wong et al, 2003). Two items not reversedworded were added based on the idea that prevention-focused people would tend to move away from danger or threats (Chen & Bei, 2017). In English, the two items would be "Growing up, I would act in ways to avoid getting into trouble" and "Compared to most people, I typically opt for safe choices."…”
Section: Sample and Proceduresmentioning
confidence: 99%